Fetal‐TAPSE for Surveillance of Cardiac Function in Growth‐Restricted Fetuses With a Portosystemic Shunt. (11th January 2021) - Bardin, Ron; Perlman, Sharon; Hadar, Eran; Mozer Glassberg, Yael; Bruckheimer, Elchanan; Silber, Michal; Gilboa, Yinon
Abstract : Objectives: Congenital portosystemic shunt (CPSS) in a growth‐restricted fetus may lead to cardiac overload and ultimately hemodynamic imbalance. The aim of the study was to describe the application of tricuspid annular plane systolic excursion (TAPSE) for surveillance of cardiac function in growth‐restricted fetuses diagnosed with CPSS. Methods: The study group consisted of 7 fetuses with growth restriction diagnosed with CPSS between 2018 and 2020. Patients were followed longitudinally every 2 weeks. Sonographic fetal‐TAPSE (f‐TAPSE) was performed every 2 weeks. At each visit, the following parameters were recorded: estimated fetal weight, biophysical profile, nonstress test, Doppler flow indices, and fetal cardiothoracic index. Postnatal laboratory and imaging tests were retrieved from the medical files. Results: Mean gestational age at diagnosis of CPSS was 32 + 1 weeks. Cardiomegaly was observed in all cases. All portosystemic shunts were classified as intrahepatic. Values of f‐TAPSE were above the 95th percentile in 6/7 fetuses at presentation and throughout follow‐up. Gestational age at delivery ranged between 36 + 5 and 38 + 5 weeks. Postnatally, spontaneous closure of the shunt was noted in 2 infants. Transient hyperammonemia was diagnosed in 2 neonates, with no signs of the characteristic complication. Conclusions: In growth‐restricted fetuses diagnosed concomitantly with CPSS, f‐TAPSE offers a practical sonographic tool for assessment of cardiac function and may serve as an additional clinical marker for follow‐up. The appearance of cardiomegaly in growth‐restricted fetuses should prompt a dedicated sonographic evaluation of the fetal portal system.